Effects of Edaravone, a Free Radical Scavenger, on Photochemically Induced Cerebral Infarction in a Rat Hemiplegic Model - Satoshi Ikeda; Katsuhiro Harada; Akihiko Ohwatashi; Yurie Kamikawa (The Scientific World Journal)
Edaravone is a free radical scavenger that protects the adjacent cortex during cerebral infarction. We created a hemiparetic model of cerebral thrombosis from a photochemically induced infarction with the photosensitive dye, rose bengal, in rats. We examined the effects of edaravone on recovery in the model. A total of 36 adult Wistar rats were used. The right sensorimotor area was irradiated with green light with a wavelength of 533 nm (10 mm diameter), and the rose bengal was injected intravenously to create an infarction. The edaravone group was injected intraperitoneally with edaravone (3 mg/kg), and the control group was injected with saline. The recovery process of the hemiplegia was evaluated with the 7-step scale of Fenny. The infarcted areas were measured after fixation. The recovery of the paralysis in the edaravone-treated group was significantly earlier than that in the untreated group. Seven days later, both groups were mostly recovered and had scores of 7, and the infarction region was significantly smaller in the edaravone-treated group. Edaravone reduced the infarction area and promoted the functional recovery of hemiparesis from cerebral thrombosis in a rat model. These findings suggest that edaravone treatment would be effective in clinical patients recovering from cerebral infarction.